Tren Global Penelitian Konseling Daring dan Kesehatan Mental di Era Digital: Analisis Bibliometrik 2015–2025 - Syarifah Rahmah (Jurnal Muria Research Guidance and Counseling (MRGC), 2026)
This study aims to map global research trends on online counseling and mental health in the digital era using a bibliometric approach. Data were obtained from the Scopus database using the keywords "online counseling," "e-counseling," "telecounseling," and "cyber counseling" combined with "mental health" for the period 2015–2025, resulting in 295 documents. Analysis was conducted using Scopus descriptive features and VOSviewer to visualize keyword co-occurrence networks. The findings show a sharp increase in publications in 2020 due to the COVID-19 pandemic, peaking in 2022 and remaining stable afterward. The United States, Australia, and the United Kingdom dominate publications, with Indonesia ranked among the top contributors. Keyword analysis highlights cognitive behavioral therapy and psychology as dominant themes, while artificial intelligence, chatbots, and language models emerge as recent trends. The study underscores the growing role of technology in online counseling and the need for greater contributions from Indonesian researchers.